History Taking as a Diagnostic Tool in Children With Chronic Cough - Kantar, Ahmad; Marchant, Julie M.; Song, Woo-Jung; Shields, Michael D.; Chatziparasidis, Grigorios; Zacharasiewicz, Angela; Moeller, Alexander; Chang, Anne B. (Frontiers in Pediatrics, 2022)
Chronic cough is a common symptom of many underlying respiratory and non-respiratory disorders and may be associated with less serious causes, such as gastroesophageal reflux and nasal diseases. Chronic cough in children differs from that in adults with respect to its aetiologies and management since it can indicate a symptom of an underlying disease in children. Guidelines for managing chronic cough in children are based on recording the history, followed by physical examination, chest radiography, and spirometry. Thus, taking accurate respiratory history for coughing helps delineate the pathophysiological basis of the cause of chronic cough. Detailed history taking enhances the evaluation and treatment, and facilitates a tailored diagnostic identification of likely diagnoses. While studies have described evidence-based red flags in children with chronic cough, the value of skilled physicians regarding history taking has received less attention for the best patient care. In the present article, we outline the major questions comprising a detailed history taking for chronic cough in children.